Nagaia - Siti Shahida, Kamel (Perpustakaan Negara Malaysia, 2025)
FASA 6.0: Malaysia Negaraku is a landmark international photography exhibition organized by the Department of Photography and Creative Imaging, Universiti Teknologi MARA (UiTM) Perak, in collaboration with Humanika Artspace, Bandung, Indonesia. Held in 2024, this sixth installment of the FASA series showcases 27 photographic works from a diverse group of artists—students, lecturers, and alumni—each offering a unique interpretation of Malaysian identity and culture.